(untitled) (The Nepali Mathematical Sciences Report, 2024)
This work aims to evaluate double integrals involving generalized hypergeometric functions.The integration of generalized hypergeometric functions, which extends the classical Gauss hypergeometric function pFq plays a crucial role in various areas of mathematical analysis. We explore both definite and indefinite double integrals, highlighting special cases where the results can be expressed in simple form. These integrals offer valuable insights into the structure and properties of the hypergeometric function, with potential implications for various areas ofmathematical analysis.